Peculiarities of Rendering English Phrasal Verbs into Ukrainian - Vorobiova, Oksana; Fedorenko, Yuliia; Kupar, Maiia; Martirosyan, Ludmila (International Journal of Engineering and Technology, 2018)
The article studies English phrasal verbs in the aspect of translation. The subject of the paper appears to be of particular scientific interest as it concerns English phrasal verbs – complex combinations like to dash out, to count out, consisting of a monolexemic verb and a second component of a special adverbial and prepositional nature, which tend to be non-equivalent translation units, i.e. have no direct correspondences (equivalents) in the target language. The present study based on the particular empirical material (phrasal verbs with postpositive component out) suggests an attempt to single out and illustrate the principal ways of rendering verbal complexes under consideration into the Ukrainian language. The research carried out enables to distinguish two ways of translating the lexical units in question – morphological and syntactic. Morphological way implies rendering phrasal verbs by means of predominantly Ukrainian prefixal verbs, less likely – non-prefixal verbs, and syntactical – with the help of free or stable word combinations. It has been established that the translation ways indicated, on their turn, reflect the peculiarities of the typological status phrasal verb possesses in the English language, as it can serve as a compound/analytical verb with postpositive component in the function of the derivation formant or be used as a more or less free combination of a verb and a postpositive element of a distinct adverbial character. The assumption has been made that it is not only the categorical status of the phrasal verb that influences the choice of the way of its translation, but also the semantic type phrasal verbs under analysis refer to.